CHARACTERIZATION OF CITHOSAN FROM MILKFISH SCALES (CHANOS CHANOS) AS A RAW MATERIAL FOR BIOPLASTICS - Putri Izzati Zakaria; Esti Tyastirin (Universitas PGRI Sumatera Barat, 2025)
Milkfish (Chanos chanos) scales are a fishery waste rich in chitin and have the potential to be processed into chitosan as a raw material for environmentally friendly bioplastics. This study was conducted using a descriptive qualitative approach through a literature review of seven recent scientific journals. The analysis results show that chitosan derived from milkfish scales has a degree of deacetylation ranging from 44%-92.71%, yield of 20.26%-31.81%, ash content of 0.99%-3.9%, and moisture content of 16%-20%. Physically, chitosan appears as an off-white to yellowish fine powder, odorless, and soluble in acetic acid, thus meeting most of the SNI 7949:2013 standards. This study aims to evaluate the characteristics of milkfish scale-derived chitosan as a raw material for bioplastic production.